Impressive Insults: How do consumers perceive self-deprecating advertisements? - Sayin, Eda; Kale, Vaishnavi (Wiley, 2024)
Most advertisements highlight a product's positive attributes to attract consumers. Yet, some brands deliberately criticize themselves by employing self-deprecation within their communications, such as Carlsberg's “Probably not the best beer in the world” campaign. This research examines whether, when, and why consumers react more favorably to self-deprecating advertisements. In six experiments, we demonstrate that when the self-deprecated attribute holds less importance to consumers, self-deprecating (vs. self-promoting) advertisements enhance brand trust by elevating the brand's social attractiveness and diminishing consumer skepticism. Importantly, self-deprecation in advertisements also lowers consumers' tendency to avoid them. We empirically rule out several alternative explanations (i.e., consumer engagement, sentiment, nonconformity, and novelty) for these effects. Our research builds on prior studies in impression management and social psychology, contributing to the literature on advertising, self-deprecation, and consumer skepticism by promoting the strategic use of self-deprecating advertisements to bolster brand trust and reduce advertising avoidance. We offer actionable insights for managers and practitioners, highlighting how self-deprecation can effectively address the challenges of building trust in diverse consumer-facing marketing contexts.
Keywords: Self-deprecation; Social attractiveness; Brand trust; Consumer skepticism; Advertising avoidance; ODS 4 - Educación de calidad